A Study on the Assessment of Nutritional Knowledge and Attitudes among Sports Persons - Khan, Kayamkani Abedulla (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: For athletes a good and balanced diet is of great importance and a key to success. To meet athletes’ energy requirements training, competition and recovery athletes must fuel their bodies with the appropriate nutritional foods. If these food diet requirements are not fulfilled, there is a high risk of very poor performance, outcome, and health problems. Objective: This investigation was just to compare the nutrition attitude and knowledge of sports persons in Jeddah city, which is very close to Holy city Makkah. Materials and Methods: This study was a cross-sectional survey was conducted over 12 weeks from February to April 2018 in Jeddah city, Kingdom of Saudi Arabia. Nutritional knowledge was assessed using the online electronic questioners were circulated to the athletes aged between 18 and 35 years and willingness to participate in the study in Jeddah, Saudi Arabia. Results and Discussion: A total of 248 athletes, including both male and females were participated in our study. The females are participate majority number in our study 72% (n = 179) and 28% (n = 69) males are participated. Our study shows that 38.5 % (n = 96) 3–4 days a week, the participants engaged in the sports. Maximum respondents are currently free from health issues 54.9% (n = 136) and 28% (n = 69) are with obesity. Conclusion: This study revealed that the use of a nutritional supplement within established guidelines is safe, effective, and ethical. It is very important to educate the sportsmen regarding the dietary pattern. Failure to consume proper diet during competition due to false belief in markets and constant fear of eating prohibited foodstufff may hamper performance. Finally, the future of nutritional supplement looks very bright in regard to the areas of the transport mechanism, improved muscle retention as well as treatment of numerous clinical maladies through supplementations.